Clinical significance of the genus Weissella: a brief review - Svishcheva M.V.; Kolesnikova E.A. (Клиническая микробиология и антимикробная химиотерапия, 2025)
This review provides the characteristics of representatives of the Weissella genus, including W. confusa, W. cibaria, and W. viridescens. The morphological, cultural, biochemical serological properties of these microorganisms belonging to the genus Weissella were described. It also discussed the unique aspects of their microecology and the challenges associated with their identification in clinical practice. Clinical cases resulting from infections caused by representatives of the Weissella genus are examined, with a particular focus on the manifestations and progression of the associated diseases. Importantly, these pathogens pose a significant threat to immunocompromised patients, individuals with chronic illnesses, and those who have undergone hematopoietic stem cell, liver, or skin graft transplantation, as well as elderly patients. Furthermore, it has been observed that Weissella genus representatives exhibit resistance to antibiotics such as vancomycin, cefotaxime, levofloxacin, metronidazole, teicoplanin, imipenem, and meropenem.